Physicochemical and Nutritional Characterization of Brebas for Fresh Consumption from Nine Fig Varieties (Ficus carica L.) Grown in Extremadura (Spain) - Cristina Pereira; Margarita López Corrales; Alberto Martín; María del Carmen Villalobos; María de Guía Córdoba; Manuel Joaquín Serradilla (Journal of Food Quality)
The quality characteristics of brebas for fresh consumption from nine fig varieties at different commercial ripening stages were determined. Physicochemical and nutritional parameters were analyzed for both skin and flesh, and the findings were compared among varieties and ripening stages. The results revealed that the major nutrient components in brebas are sugars, such as glucose and fructose, and mineral elements, including K, Ca, P, and Mg. Most nutrients evaluated are important elements that contribute to the commercial quality of brebas. “Brown Turkey” and “Banane” varieties showed the highest weight and width. The concentrations of the monomer sugars studied were higher in flesh than skin, and the “Cuello Dama Blanco” and “Colar Elche” varieties showed the highest content of these sugars. The early ripening stage, coinciding with a fast increase in fruit size, was also associated with a higher fiber and protein contents, TA, and firmness for “Banane,” “Brown Turkey,” and “Blanca Bétera” varieties. Conversely, the later ripening stage was related to a significant increase of TSS, MI, and color intensity. Finally, no clear changes in the concentrations of organic acids were observed between different varieties and commercial ripening stages.